Acute anterior uveitis after yersinia infection. Issue 3 (March 1982) - Mattila, L; Granfors, K; Toivanen, A
Abstract : Twenty-eight cases of acute anterior uveitis in which raised antibody titres indicated yersinia infection as a possible causative factor in the disease were studied retrospectively. In most cases the antibodies belonged to the IgA class; in only 6 patients did the presence of IgM class antibodies indicate recent infection. In half the cases also antibody titres against Chlamydia were raised. The clinical features and course of the disease did not differ from those of acute anterior uveitis due to other causes.